KOMPARASI PENERAPAN PRINSIP KONSERVATISME PADA AKUNTANSI KONVENSIONAL DAN AKUNTANSI SYARIAH - ANITA WAHYU ALVIANI; HUSNUL KHOTIMAH; YOLANDA SRYTA PRADANI; AHMAD ULIL ALBAB AL UMAR; NUR KABIB (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to analyze whether there is difference between conservatism of conventional accounting and sharia accounting. Conservatism is an important principle in financial reporting which can be seen on how an entity recognize an earning increase with delay while they recognize an earning decrease on timely basis. Conservatism is a prudent reaction in accounting. From the results of the analysis, it can be concluded that there is no significant difference between accounting conservatism in conventional accounting and sharia accounting. But I found that sharia accounting report the transactions more conservatively than the conventional one. Differences in the level of conservatism in Sharia Commercial Banks and Conventional Commercial Banks are influenced by the higher litigation risk that is faced by the Sharia Commercial Banks and the obligation to pay Zakah.